Improving Care for Patients with Chronic Obstructive Pulmonary Disease, Holistic and All-Dimensional by the Participation of Health Service Network, Ban Hong District, Lamphun Province - Yasamut, Pornwipa; Meamma, Wipaphun; Srisuwannophakul, Pisamai; Promarat, Chortip; Wongprom, Nuntana; Chotinun, Aroonwadee (Journal of Health Science of Thailand, 2020)
The objective of this research was to develop a model for improving care for patients with chronic obstructive pulmonary disease (COPD), using the holistic and all-dimensional approaches through participation of the health service network, Ban Hong District, Lamphun Province. It was conducted in the fiscal years 2015-2017. The study samples included 555 COPD patients and 41,357 healthy people in the study area. Data collected were variables to be used for the analysis of re-visit rates, re-admission rates), and the expenses. The study was a continuation of a series of patient care process began in 2007 of which the evidence-based practice was applied as a development tool. All the constraints and problems identified in all early phases were addressed in the current study which was operated both inside and outside the hospital covering patients, families, communities in order to maintain high quality of care for the COPD patients with the main focus on health promotion, prevention, treatment, rehabilitation, palliative and end of life care. Participation of the local health service network was taken into consideration throughout the process with the expectation on sustainability of the care. It was found that the health service network had contributed significantly, and many initiatives were developed that covered the whole spectrum of holistic care (physical, emotional, social, and spiritual) and health care (health promotion, prevention, treatment, rehabilitation, palliative and end of life care). All such development activities had resulted in the better outcomes of care for the COPD patients as identified by the reduction of re-visit rates and the health care costs. The study outcomes indicated that successful and sustainable development required cooperation among all relevant parties, and covered the holistic and all-dimensional care. Consistent situation assessment and continued commitment are also essential. In this regard, routine to research (R2R) could be a useful tool in the development process.